You want to get y by itself.
First, let's move the 4x^2 over.
-4x^2 + 4x^2 + 9y^2 = -4x^2 + 36
0 + 9y^2 = -4x^2 + 36
9y^2 = 36 - 4x^2
Next, let's multiply both sides by (1/9) to remove the 9 from the left hand side:
(1/9)*9y^2 = (1/9)(36 - 4x^2)
1*y^2 = 36/9 - (4/9)x^2
y^2 = 4 - (4/9)x^2
Next, take the square root of both sides:
(y^2)^(1/2) = (4 - (4/9)x^2)^(1/2)
|y| = Sqrt[(4/9)(9-x^2)]
|y| = Sqrt[4/9]*Sqrt[9-x^2]
|y| = (2/3)*Sqrt[9-x^2]
Finally, get y by itself by using the definition of absolute value:
y = +/- (2/3)*Sqrt[9-x^2]
I think your answer is off by a factor of 1/3.
2007-01-07 12:00:08
·
answer #1
·
answered by alsh 3
·
0⤊
0⤋
Hi,
Subtract 4x^2 from both sides. You now have:
9y^2 = 36 - 4x^2
Now divide everything by 9 and factor a 4 out of the right side. You'd have:
y^2 = 4(9 - x^2)/9
Now take the square root of both sides of the equation and put + or - in front of the radical on the right side. You get:
y = + or - square root((4(9 - x^2))/9) which simplifies to:
y = + or - 2/3 square root(9 - x^2). In your answer you missed the 3 in the denominator outside of the radical.
I hope that helps.
2007-01-07 20:09:05
·
answer #2
·
answered by Pi R Squared 7
·
0⤊
0⤋
4x^2+9y^2 = 36
9y^2 = 36 - 4x^2
y^2 = 4 - 4/9x^2
y = +/- sqrt( 4 - 4/9x^2)
y = +/- 2 sqrt( 1 - 1/9x^2)
If I did this correctly then your answer is not exactly correct, but close. The sqrt must include the x^2 parameter as my answer reflects.
2007-01-07 20:00:27
·
answer #3
·
answered by rscanner 6
·
0⤊
0⤋
Substitute your answer into the original equation and you should get an Identity 36=36, but you don't. Your answer is incorrect.
The correct answer is y=(SQRT(36-4X^2))/3.
Make the substitution and you will get an Identity
thereby proving it all by yourself.
2007-01-07 20:26:06
·
answer #4
·
answered by ? 5
·
0⤊
0⤋
That's not a solution!
The general form of the formula is: x^2 + y^2 = r^2
It's the formula for a circle, of radius r.
Your formula becomes: (2x)^2 +(3y)^2 = 6^2
It's a distorted circle (ellipse), of radius 6.
2007-01-07 20:02:20
·
answer #5
·
answered by Alan 6
·
0⤊
0⤋
well when i tried solving it i got y=-2/3x + 2 but hey i dont know.
2007-01-07 20:01:46
·
answer #6
·
answered by Islandgirl 1
·
0⤊
0⤋
there were just finding the answer in terms of y...so they moved everything to the other side to get y by itself....the last step they did was get rid of the exponent of y
2007-01-07 20:23:21
·
answer #7
·
answered by ? 2
·
0⤊
0⤋